Sodium ion battery negative electrode material, pretreatment method and prepared sodium ion battery
By pretreating the negative electrode material of the sodium ion battery, a stable electrode electrolyte interface is formed, which solves the problem of SEI instability in sodium ion batteries, significantly improves the battery's Coulomb efficiency and capacity retention rate, and improves the long-term cycle of the battery performance.
Patent Information
- Application Number
- CN202410825259.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-25
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-06-25
AI Technical Summary
The instability of the electrode-electrolyte interface (SEI) in sodium ion batteries leads to decay of battery performance, affecting long-term circulation performance and energy density. Moreover, SEI is easily soluble in electrolyte and cannot meet the stable circulation requirements of sodium ion batteries.
By pretreating the negative electrode material of the sodium ion battery, a stable, insoluble SEI is formed. The method includes constructing a pretreatment battery system with high concentration electrolyte, performing charge and discharge cycles to form a stable electrode electrolyte interface, preferably using hard Carbon or copper electrode material, and an electrode electrolyte interface is formed in high concentration electrolyte to ensure interface stability.
The high first-week Coulomb efficiency and long-term circulation performance improvement of sodium ion batteries have been achieved. The average Coulomb efficiency reaches 99.95%, and the capacity retention rate reaches 80%, which significantly improves the stability and performance of the battery.
Smart Images

Figure CN119133351A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a sodium ion battery negative electrode material, a pretreatment method and a prepared sodium ion battery, and belongs to the field of sodium ion batteries. Background Art
[0002] Energy is an important driving force for social development. Since fossil fuels are non-renewable, it is crucial to develop new energy systems. New energy sources include solar energy, wind energy, and chemical energy. Solar energy and wind energy are difficult to achieve stable and continuous energy supply, and the equipment is expensive, so chemical energy has become the most practical new energy. Among chemical energy sources, lithium-ion batteries have attracted widespread attention due to their high energy density and long cycle period, and are currently successfully used in portable electronic devices and other aspects. However, in recent years, the explosive growth in demand for lithium-ion batteries in electric vehicles and large-scale energy storage grids has formed an increasingly prominent supply and demand contradiction with the current situation that lithium resources are less in the earth's crust, unevenly distributed, and expensive. Therefore, it is necessary to find a substitute for lithium-ion batteries. Sodium reserves are abundant, and sodium-ion batteries have a similar working mechanism to lithium-ion batteries. They can be commercially produced using existing lithium-ion battery production lines, so sodium-ion batteries are the most promising secondary ion batteries.
[0003] However, compared with lithium-ion batteries, sodium-ion batteries currently have a lower energy density, and the instability of the solid-electrolyte interphase (SEI) limits their long-term cycle performance, hindering further commercial applications. The improvement of the energy density of sodium-ion batteries is mainly focused on the development of high-energy-density positive and negative electrode materials, such as alloyed negative electrodes. The instability of the electrode-electrolyte interface (SEI) is an important reason for the degradation of battery performance, and this problem is more prominent in sodium-ion batteries than in lithium-ion batteries. There is an urgent need for basic scientific mechanism analysis and breakthroughs in actual cycle performance. SEI is a passivation layer formed when the negative electrode contacts the electrolyte and the electrolyte is reduced. The ideal electrode-electrolyte interface should meet the following requirements: (1) Allow Na ions to migrate to form a battery circuit; (2) Insulate electrons to avoid side reactions and continuous consumption of sodium sources; (3) The electrolyte molecules cannot contact the electrode through SEI, avoiding further reactions between the electrode and the electrolyte. Unstable SEI may bring about a series of side reactions, leading to electrolyte depletion, while consuming sodium sources, reducing the battery coulombic efficiency, thereby affecting the long-term cycle performance of the battery and reducing the actual capacity retention rate of the battery; finally, unstable SEI may have high and uneven interface impedance, hindering the migration of sodium ions and affecting the rate performance of the battery. Therefore, interface instability is a key issue that hinders the improvement of battery performance.
[0004] Compared with lithium-ion batteries, one of the main reasons why SEI in sodium-ion batteries is difficult to exist stably is that the SEI components in sodium-ion batteries are more soluble in the electrolyte, which cannot meet the requirements of long-term stable circulation of sodium-ion batteries. The dissolution of SEI consumes the limited sodium source in the whole battery and accelerates the depletion of the electrolyte, causing irreversible capacity decay of sodium-ion batteries and even battery failure. How to stabilize the SEI on the surface of the negative electrode material is an important problem that sodium-ion batteries need to solve. Summary of the invention
[0005] In order to solve the problem that the dissolution of SEI on the surface of the negative electrode material of the sodium ion battery leads to the weakening of the performance of the sodium ion battery, the present invention provides a negative electrode material for a sodium ion battery, a pretreatment method for the negative electrode material of a sodium ion battery, and a corresponding sodium ion battery based on the above. The negative electrode material provided is to pretreat the negative electrode material body first, form a layer of SEI on the surface, and then use it as the negative electrode material of the commercial sodium ion battery. The treated negative electrode material has a stable and non-dissolving SEI, and the coulomb efficiency of the formed sodium ion battery reaches 90.29% in the first week, and the average coulomb efficiency reaches 99.95% after 900 cycles.
[0006] The technical solution adopted is: a pretreatment method for a negative electrode material of a sodium ion battery, comprising the following steps:
[0007] Obtaining a negative electrode material body;
[0008] Constructing a pre-treatment battery system: constructing a pre-treatment battery system with the negative electrode material body as the working electrode, the concentration of the electrolyte in the pre-treatment battery system is greater than the concentration of the electrolyte in the target battery system, the pre-treatment battery system is a battery system for pre-treating the negative electrode material body, the pre-treatment battery system is a sodium ion battery, and the target battery system is a battery system to be constructed with the pre-treated negative electrode material body as the negative electrode;
[0009] Performing a charge-discharge cycle on the pre-processed battery system: performing a charge-discharge cycle on the constructed pre-processed battery system to form an electrode electrolyte interface on the negative electrode material body;
[0010] The negative electrode material body is taken out to obtain the pretreated negative electrode material.
[0011] As a preferred embodiment, the pretreatment battery system is constructed in one of the following ways: (1) using the negative electrode material as the working electrode and sodium metal as the counter electrode to construct a half-battery system; (2) using the negative electrode material as the negative electrode and the sodium battery positive electrode material as the positive electrode to construct a full-battery system.
[0012] As a preferred solution, the concentration of the electrolyte in the pretreatment battery system is higher than 1.8 mol / L, preferably higher than 4 mol / L. The electrode electrolyte interface formed at this high concentration has a very low organic content and a very high inorganic content. The SEI has extremely low solubility in the solvent and high interface stability.
[0013] As a preferred embodiment, the negative electrode material body is a hard carbon electrode material or a copper electrode material; when the hard carbon electrode material is used as the negative electrode material body, the sodium ion battery system is charged and discharged at a current of (0.1-1) C (1C = 300 mAh / g) and a voltage of (0.0002-2) V, and a stable electrode electrolyte interface can be formed by charging and discharging at this current and voltage; when the copper electrode material is used as the negative electrode material body, the sodium ion battery system is charged and discharged at a current of (5-100) μA and a voltage of (0.0002-2) V, and a stable electrode electrolyte interface can be formed by charging and discharging at this current and voltage. It is further preferred that during the charge and discharge cycle of the pretreatment battery system, the number of cycles is at least 1, preferably 3 or more, and more preferably 3, to ensure a sufficient number of cycles to improve the first cycle coulomb efficiency while taking into account the convenience of operation.
[0014] As a preferred embodiment, the electrolyte components in the pretreatment battery system are the same as or different from the electrolyte components in the target battery system, and the electrolyte of the pretreatment battery system or / and the target battery system includes a sodium salt and a solvent, the solvent is an organic solvent, and the sodium salt and the solvent at least meet one of the following requirements:
[0015] The sodium salt is a combination of one or more of sodium hexafluorophosphate, sodium bis(fluorosulfonyl)imide, sodium nitrate, sodium perchlorate, sodium bis(trifluoromethylsulfonyl)imide, sodium trifluoromethanesulfonate, sodium chloride, sodium tetrafluoroborate, sodium methanesulfonate, sodium trifluoromethylsulfonate, sodium bis(oxalatoborate), sodium difluorooxalatoborate, sodium difluorophosphate, sodium difluorobis(oxalatophosphate), and sodium hexafluoroarsenate, and preferably sodium bis(fluorosulfonyl)imide, sodium hexafluorophosphate, and sodium perchlorate. This type of sodium salt has high solubility in solvents, can form a high-concentration electrolyte, and is conducive to the formation of a stable SEI;
[0016] ——The solvent is a combination of one or more of ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, propylene carbonate, diethyl carbonate, dioxolane, ethyl methyl carbonate, dimethyl carbonate, vinylene carbonate, fluoroethylene carbonate, and tetrahydrofuran; preferably, the sodium salt in the pretreatment battery system is sodium bis(fluorosulfonyl)imide, and the solvent is ethylene glycol dimethyl ether.
[0017] The preparation method of the hard carbon electrode is as follows: hard carbon powder is mixed evenly with a binder (polyvinylidene fluoride (PVDF)) and a conductive agent (conductive carbon black) in a dispersant (N-methylpyrrolidone) according to a set ratio, and then coated on a conductive current collector; the coated hard carbon electrode is vacuum dried to obtain a hard carbon electrode.
[0018] As a preferred solution, the components at the electrode-electrolyte interface have a lower content of organic components and a higher content of inorganic components. Specifically, in the interface components, the atomic weight content of carbon atoms is less than 60%, and preferably the atomic weight content of carbon atoms is less than 50%. Under this setting, the solubility of the electrode-electrolyte interface in the solvent and the electrolyte is extremely low. Even if immersed for more than 50 hours, the capacity loss of the interface can still be guaranteed to be less than 1.5μAh.
[0019] On the other hand, the present invention provides a sodium ion battery negative electrode material, the negative electrode material body surface contains a preformed electrode electrolyte interface. The electrode electrolyte interface is formed in a high concentration electrolyte, preferably the organic component content is less than 70%; after the electrode electrolyte interface is immersed in an organic solvent for 50 hours, the component loss rate in the electrode electrolyte interface is less than 15%; the carbon content in the components of the electrode electrolyte interface is less than 60%, preferably less than 50%, the lower organic component and the higher inorganic component effectively inhibit the dissolution of the interface component in the electrolyte, thereby ensuring the stability of the interface, when the carbon element is less than 50%, the carbon element can be almost not reduced when the interface is immersed in the electrolyte, and when the carbon element content is 64%, under the same immersion conditions, the C element content is reduced by about 24%, so ensuring that the C element content is less than 50% can greatly improve the stability of the interface.
[0020] The sodium ion battery negative electrode mentioned in the above scheme can be obtained by the pretreatment method of the above negative electrode material.
[0021] On the other hand, the present invention also provides a sodium ion battery, which is constructed by using the pretreated sodium ion battery negative electrode material prepared in the above scheme as the negative electrode, specifically a commercial sodium ion full battery, using a commercial electrolyte with a concentration of 1 mol / L, and more preferably, using a hard carbon electrode as the negative electrode and a manganese iron nickel layered oxide as the positive electrode to construct the full battery. The preparation process is shown in Figure 1 First, a hard carbon electrode was assembled with sodium metal and 4 mol / L sodium bis(fluorosulfonyl)imide in ethylene glycol dimethyl ether to form a battery for pretreatment of the negative electrode material. After the battery was cycled 3 times, the negative electrode material was taken out and assembled into a full battery according to the above-mentioned commercial sodium ion full battery assembly method.
[0022] The beneficial effects of the present invention include: the negative electrode material in the present invention forms a stable electrode electrolyte interface that is not easily dissolved after pretreatment, the inorganic component on the interface is relatively high and the organic component is relatively low, so that the electrode electrolyte interface as a whole is not easily dissolved in the electrolyte, and the prepared full battery has a capacity retention rate of 80% after 900 charge and discharge cycles, and an average coulomb efficiency of 99.95%. More detailed beneficial effects are described in the specific implementation method section. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 Schematic diagram of the assembly process of a full battery;
[0024] Figure 2 Capacity loss of batteries corresponding to different negative electrode materials;
[0025] Figure 3 Cumulative capacity loss of batteries corresponding to different negative electrode materials;
[0026] Figure 4 Normalized sodium ion concentration of different anode materials after immersion in solvents;
[0027] Figure 5 Element content of different negative electrode materials;
[0028] Figure 6 Changes in element content of different negative electrode materials after being immersed in electrolyte;
[0029] Figure 7(a), Figure 7(b) and Figure 7(c) show the dissolution of the electrode electrolyte interface at different concentrations;
[0030] Figure 8 The first week charge and discharge curves of the full battery with and without pretreatment of the negative electrode material;
[0031] Fig. 9 The negative electrode materials with and without pretreatment correspond to long cycles of full batteries;
[0032] Fig.10 Coulombic efficiency of the full battery with and without pretreatment of the negative electrode material. DETAILED DESCRIPTION
[0033] The present invention is further explained in detail below in conjunction with the accompanying drawings and specific embodiments, but it should be understood that the protection scope of the present invention is not limited by the specific embodiments.
[0034] In order to improve the stability of the sodium ion battery, the present invention pre-treats the negative electrode material of the sodium ion battery, and assembles the pre-treated negative electrode material into a sodium ion battery. Compared with the untreated sodium ion battery, the coulombic efficiency is greatly improved.
[0035] The pretreatment method of the negative electrode material in the present invention comprises the following steps: (1) obtaining the negative electrode material body; (2) constructing a pretreatment battery system; (3) performing a charge-discharge cycle on the pretreatment battery system; (4) taking out the negative electrode material body to obtain the pretreated negative electrode material. Assembling the target battery with the pretreated negative electrode material can improve the performance of the target battery. The pretreatment method is further described in detail below.
[0036] Obtaining the negative electrode material body: The negative electrode material used in conventional sodium ion batteries can be purchased directly or prepared by oneself. In order to obtain a negative electrode material with better performance, it is preferably prepared by oneself. The negative electrode material body is preferably a copper electrode and a hard carbon electrode. These two electrode materials have high stability. The copper electrode is suitable for mechanism research, and the hard carbon electrode is suitable for building a full battery. The copper electrode is a copper foil cut into a certain size, and the purity of the copper foil is higher than 99.9%, and the thickness is 5-20um; the hard carbon electrode is made of hard carbon powder, polyvinylidene fluoride (PVDF), and conductive carbon black (super P) in a mass ratio of 85:8:7, mixed evenly in N-methylpyrrolidone (NMP), and coated on an aluminum foil current collector. The coated hard carbon electrode is vacuum dried at 110 degrees Celsius for 12 hours to obtain a hard carbon electrode.
[0037] Constructing a pretreatment battery system: The pretreatment battery system is used to pretreat the negative electrode material body. The pretreatment battery system is a sodium ion battery, which can be a full battery or a half battery. If it is a full battery, the negative electrode material body to be treated is used as the negative electrode, the conventional sodium ion battery positive electrode material is used as the positive electrode, and the set sodium salt solution is used as the electrolyte to obtain the pretreatment full battery. The sodium ion battery positive electrode material can be a layered oxide positive electrode material, a polyanion positive electrode material, a Prussian blue analog positive electrode material, or an organic positive electrode material; if it is a half battery, the negative electrode material body to be treated is used as the working electrode, the sodium metal with metallic luster is used as the counter electrode and the reference electrode, the glass fiber purchased on the market is used as the battery separator, and the set sodium salt solution is used as the electrolyte to assemble to form a half battery, such as a button battery, a soft pack battery, etc. Regardless of whether the pretreatment battery system is a full battery or a half battery, the electrolyte concentration is greater than the electrolyte concentration of the target battery system. The target battery system is a sodium ion battery in which the pretreated negative electrode material will eventually act as the negative electrode. The electrolyte of the pretreatment battery system is the same as or different from the electrolyte of the target battery system, and is a mixture of sodium salt and organic solvent, and the sodium salt is selected from sodium hexafluorophosphate (NaPF6), sodium bis(fluorosulfonyl)imide (NaFSI), sodium nitrate (NaNO3), sodium perchlorate (NaClO4), sodium bis(trifluoromethylsulfonyl)imide (NaTFSI), sodium trifluoromethanesulfonate (NaOTf), sodium chloride (NaCl), sodium tetrafluoroborate (NaBF4), sodium methanesulfonate (NaCH3SO3), sodium trifluoromethanesulfonate (NaCF3SO3), sodium bis(oxalatoborate) (C4BNaO8), difluorooxalate At least one of sodium borate (C2BF2NaO4), sodium difluorophosphate (NaPO2F2), sodium difluorobis(oxalyl)phosphate (NaDFBP), sodium hexafluoroarsenate (NaAsF6); the organic solvent is selected from ethylene glycol dimethyl ether (DME), diethylene glycol dimethyl ether (DEGDME), tetraethylene glycol dimethyl ether (TEGDME), propylene carbonate (PC), diethyl carbonate (DEC), dioxolane (DOL), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), vinylene carbonate (VC), fluoroethylene carbonate (FEC), tetrahydrofuran (THF). When constructing a pretreatment battery system, the preferred sodium salt is sodium bis(fluorosulfonyl)imide (NaFSI), and the solvent is preferably ethylene glycol dimethyl ether (DME). In a glove box protected by an argon atmosphere with a water oxygen value of less than 0.01ppm, the preferred sodium salt is dissolved in the preferred solvent and stirred until completely dissolved to obtain an electrolyte.
[0038] The pretreatment battery system is subjected to charge and discharge cycles: After the pretreatment battery system is constructed, an electrode electrolyte interface is formed on the negative electrode material body through charge and discharge cycles, the charge-discharge current is less than 100μA or 1C, the voltage is (0.0002-2)V, and the number of charge and discharge cycles is at least 1, preferably 3. When the negative electrode material body is a copper electrode, a current of (5-100)μA is used to circulate three times in the voltage range of (0.0002-2)V to form a thorough and stable electrode electrolyte interface. A current of preferably 5μA can more thoroughly form a stable electrode electrolyte interface. When the negative electrode material body is a hard carbon electrode, a current of (0.1-1)C is used to circulate three times in the voltage range of (0.0002-2)V to form an electrode electrolyte interface. Among them, a small current of 0.1C is preferred to form a more thorough and stable electrode electrolyte interface.
[0039] Taking out the negative electrode material body: disassembling the pre-treated battery system, taking out the negative electrode material body therein to obtain the pre-treated negative electrode material.
[0040] By using the negative electrode material obtained by the above method as the negative electrode to construct a sodium ion battery, preferably a commercial full battery, a battery system with excellent performance can be obtained.
[0041] Example 1
[0042] A method for pretreating anode materials of sodium ion batteries, comprising the following steps
[0043] (1) Obtaining the negative electrode material body: Cut the copper foil into discs with a diameter of 19 mm to obtain the negative electrode material body;
[0044] (2) Constructing a pretreatment battery system: a. Preparing an electrolyte: using sodium bis(fluorosulfonyl)imide as sodium salt and ethylene glycol dimethyl ether as solvent, fully dissolving under the protection of an argon atmosphere with a water and oxygen value less than 0.01 ppm, the concentration of sodium bis(fluorosulfonyl)imide is 4 mol / L; b. Using the negative electrode material obtained in step (1) as the working electrode, sodium metal as the counter electrode and reference electrode, and glass fiber as the battery separator, 150 μL of the electrolyte is added to assemble a button battery;
[0045] (3) performing a charge-discharge cycle: the button cell is cycled three times at a low current of 5uA in the range of 0.0002-2V to form an electrode-electrolyte interface on the surface of the negative electrode material;
[0046] (4) Take out the negative electrode material.
[0047] Example 2
[0048] A method for pretreating anode materials of sodium ion batteries, comprising the following steps
[0049] (1) Obtaining the negative electrode material: Commercial-grade hard carbon powder is mixed with polyvinylidene fluoride (PVDF) and conductive carbon black (super P) in a mass ratio of 85:8:7 in N-methylpyrrolidone (NMP) and coated on a commercial aluminum foil current collector. The coated hard carbon electrode is vacuum dried at 110 degrees Celsius for 12 hours to obtain a hard carbon electrode;
[0050] (2) Constructing a pretreatment battery system: a. Preparing an electrolyte: sodium bis(fluorosulfonyl)imide is used as the sodium salt, ethylene glycol dimethyl ether is used as the solvent, and the sodium bis(fluorosulfonyl)imide is fully dissolved under the protection of an argon atmosphere with a water and oxygen value less than 0.01 ppm. The concentration of sodium bis(fluorosulfonyl)imide is 4 mol / L; b. The negative electrode material obtained in step (1) is used as the working electrode, sodium metal is used as the counter electrode and the reference electrode, and glass fiber is used as the battery separator. 150 μL of the electrolyte is added to assemble a button cell. The sodium metal electrode is obtained by removing the outer oxide layer of the sodium metal in a glove box protected by an argon atmosphere with a water and oxygen value less than 0.01 ppm.
[0051] (3) performing charge and discharge cycles: the button cell is cycled three times at a low current of 0.1C in the range of 0.0002-2V to form an electrode-electrolyte interface on the surface of the negative electrode material;
[0052] (4) Take out the negative electrode material.
[0053] Example 3
[0054] A method for pretreating anode materials of sodium ion batteries, comprising the following steps
[0055] (1) Obtaining the negative electrode material body: Cut the copper foil into discs with a diameter of 19 mm to obtain the negative electrode material body;
[0056] (2) Constructing a pretreatment battery system: a. Preparing an electrolyte: using sodium bis(fluorosulfonyl)imide as sodium salt and ethylene glycol dimethyl ether as solvent, fully dissolving under the protection of an argon atmosphere with a water and oxygen value less than 0.01 ppm, the concentration of sodium bis(fluorosulfonyl)imide is 1 mol / L; b. Using the negative electrode material obtained in step (1) as the working electrode, sodium metal as the counter electrode and reference electrode, and glass fiber as the battery separator, 150 μL of the electrolyte is added to assemble a button battery;
[0057] (3) performing a charge-discharge cycle: the button cell is cycled three times at a low current of 5uA in the range of 0.0002-2V to form an electrode-electrolyte interface on the surface of the negative electrode material;
[0058] (4) Take out the negative electrode material.
[0059] Example 4
[0060] A method for pretreating anode materials of sodium ion batteries, comprising the following steps
[0061] (1) Obtaining the negative electrode material: Commercial-grade hard carbon powder is mixed with polyvinylidene fluoride (PVDF) and conductive carbon black (super P) in a mass ratio of 85:8:7 in N-methylpyrrolidone (NMP) and coated on a commercial aluminum foil current collector. The coated hard carbon electrode is vacuum dried at 110 degrees Celsius for 12 hours to obtain a hard carbon electrode;
[0062] (2) constructing a pretreatment battery system: a. preparing an electrolyte: sodium bis(fluorosulfonyl)imide is used as the sodium salt, ethylene glycol dimethyl ether is used as the solvent, and the electrolyte is fully dissolved under the protection of an argon atmosphere with a water and oxygen value less than 0.01 ppm, and the concentration of sodium bis(fluorosulfonyl)imide is 1 mol / L; b. the negative electrode material obtained in step (1) is used as the working electrode, sodium metal is used as the counter electrode and the reference electrode, and glass fiber is used as the battery separator, and 150 μL of the electrolyte is added to assemble a button battery, wherein the sodium metal electrode is obtained by removing the outer oxide layer of the sodium metal in a glove box protected by an argon atmosphere with a water and oxygen value less than 0.01 ppm;
[0063] (3) performing charge and discharge cycles: the button cell is cycled three times at a low current of 0.1C in the range of 0.0002-2V to form an electrode-electrolyte interface on the surface of the negative electrode material;
[0064] (4) Take out the negative electrode material.
[0065] Example 5
[0066] A method for pretreating anode materials of sodium ion batteries, comprising the following steps
[0067] (1) Obtaining the negative electrode material body: Cut the copper foil into discs with a diameter of 19 mm to obtain the negative electrode material body;
[0068] (2) Constructing a pretreatment battery system: a. Preparing an electrolyte: using sodium bis(fluorosulfonyl)imide as sodium salt and ethylene glycol dimethyl ether as solvent, fully dissolving under the protection of an argon atmosphere with a water and oxygen value less than 0.01 ppm, the concentration of sodium bis(fluorosulfonyl)imide is 0.2 mol / L; b. Using the negative electrode material obtained in step (1) as the working electrode, sodium metal as the counter electrode and reference electrode, and glass fiber as the battery separator, 150 μL of the electrolyte is added to assemble a button battery;
[0069] (3) performing a charge-discharge cycle: the button cell is cycled three times at a low current of 5uA in the range of 0.0002-2V to form an electrode-electrolyte interface on the surface of the negative electrode material;
[0070] (4) Take out the negative electrode material.
[0071] Example 6
[0072] A method for pretreating anode materials of sodium ion batteries, comprising the following steps
[0073] (1) Obtaining the negative electrode material: Commercial-grade hard carbon powder is mixed with polyvinylidene fluoride (PVDF) and conductive carbon black (super P) in a mass ratio of 85:8:7 in N-methylpyrrolidone (NMP) and coated on a commercial aluminum foil current collector. The coated hard carbon electrode is vacuum dried at 110 degrees Celsius for 12 hours to obtain a hard carbon electrode;
[0074] (2) Constructing a pretreatment battery system: a. Preparing an electrolyte: sodium bis(fluorosulfonyl)imide is used as the sodium salt, ethylene glycol dimethyl ether is used as the solvent, and the electrolyte is fully dissolved under the protection of an argon atmosphere with a water and oxygen value less than 0.01 ppm, and the concentration of sodium bis(fluorosulfonyl)imide is 0.2 mol / L; b. The negative electrode material obtained in step (1) is used as the working electrode, sodium metal is used as the counter electrode and reference electrode, and glass fiber is used as the battery separator. 150 μL of the electrolyte is added to assemble a button battery, and the sodium metal electrode is obtained by removing the outer oxide layer of sodium metal in a glove box protected by an argon atmosphere with a water and oxygen value less than 0.01 ppm;
[0075] (3) performing charge and discharge cycles: the button cell is cycled three times at a low current of 0.1C in the range of 0.0002-2V to form an electrode-electrolyte interface on the surface of the negative electrode material;
[0076] (4) Take out the negative electrode material.
[0077] Example 7
[0078] The negative electrode material obtained in Example 2 was used as the negative electrode to assemble a full battery, the positive electrode material of the full battery was a manganese-iron-nickel-based layered oxide, and the electrolyte was 1M NaPF6 in P (propylene carbonate).
[0079] The commercially available manganese iron nickel-based layered oxide powder was mixed with polyvinylidene fluoride and conductive carbon black in a mass ratio of 85:8:7 in N-methylpyrrolidone and coated on a 12 mm diameter disc-shaped aluminum foil current collector. The coated hard carbon electrode was vacuum dried at 110 degrees Celsius for 12 hours to obtain a manganese iron nickel-based layered oxide electrode.
[0080] Example 8
[0081] Assembling a full battery: The difference from Example 7 is that the negative electrode material is a hard carbon negative electrode obtained by the pretreatment method in Example 4. The specific preparation method of the hard carbon negative electrode is: commercial-grade hard carbon powder is mixed with polyvinylidene fluoride (PVDF) and conductive carbon black (super P) in a mass ratio of 85:8:7 in N-methylpyrrolidone (NMP) and coated on a commercial aluminum foil current collector. The coated hard carbon electrode is vacuum dried at 110 degrees Celsius for 12 hours to obtain a hard carbon electrode.
[0082] Example 9
[0083] The difference from Example 4 is that the concentration of the electrolyte is 1.8 mol / L.
[0084] Example 10
[0085] The only difference from Example 4 is that the concentration of the electrolyte is 3 mol / L.
[0086] Embodiment 11
[0087] The negative electrode material obtained by pretreatment in Example 9 is used to assemble a full battery, and the assembly method of the full battery is the same as that of Example 7.
[0088] Example 12
[0089] The negative electrode material obtained by the pretreatment method in Example 10 is used to assemble a full battery, and the assembly method of the full battery is the same as that of Example 7.
[0090] The following is a test of the effects of each embodiment
[0091] Effect test 1 - electrochemical capacity loss test
[0092] The negative electrode materials obtained in Example 1, Example 3 and Example 5 and metallic sodium were respectively assembled into button batteries. The electrolyte used was a solution of sodium bis(fluorosulfonyl)imide in ethylene glycol dimethyl ether. The concentration of the electrolyte in the button battery corresponding to Example 1 was 4 mol / L, the concentration of the electrolyte in the button battery corresponding to Example 3 was 1 mol / L, and the concentration of the electrolyte in the button battery corresponding to Example 5 was 0.2 mol / L. Except for the different electrolyte concentrations, the button batteries of each embodiment had the same structure. The process of standing for 50 hours - recirculating to replenish the electrode electrolyte interface - standing for 30 hours - recirculating to replenish the electrode electrolyte interface - standing for 15 hours was carried out, and the capacity loss change of each button battery was observed, as shown in FIG. Figure 2As shown in the figure, it can be seen that the dissolution loss of the button cell corresponding to 4 mol / L is the smallest in each stage, especially after 50 hours of standing, the capacity loss is only 1.2μAh, which is much lower than the other two button cells, indicating that increasing the electrolyte concentration is beneficial to reducing the capacity loss of the negative electrode material after pretreatment. The capacity loss during the cumulative standing time of 95 hours (50 hours + 30 hours + 15 hours) is as follows Figure 3 As shown, the dissolution degree of the electrode-electrolyte interface can be reflected. It can be seen from the figure that the electrode-electrolyte interface formed under 4 mol / L electrolyte has the smallest cumulative capacity loss, which means that its dissolution degree is the smallest. Effect Test 2 - Inductively Coupled Plasma Test
[0093] The negative electrode materials obtained in Example 1, Example 3 and Example 5 were respectively immersed in an equal volume of ethylene glycol dimethyl ether. After immersion for 50 hours, the sodium ion concentration in the ethylene glycol dimethyl ether was tested. The sodium ion concentration in the test solvent can characterize the dissolution degree of the electrode electrolyte interface in the corresponding negative electrode material, and then intuitively obtain its stability. The results are as follows Figure 4 As shown, we normalized the solubility of the negative electrode material corresponding to 4 mol / L in DME to 1 unit by ICP test. The sodium ion concentrations of the negative electrode material corresponding to 1 mol / L and the negative electrode material corresponding to 0.2 mol / L in the solvent are much greater than those of the negative electrode material corresponding to 4 mol / L, which are 3.38 times and 3.26 times respectively. It can be seen that the negative electrode material treated with high concentration electrolyte has high stability.
[0094] Effect test three - X-ray photoelectron spectroscopy (XPS) test
[0095] XPS was used to test the element distribution at the electrode electrolyte interface in the negative electrode materials obtained in Example 1, Example 3 and Example 5. Figure 5 As shown, it can be seen that with the increase of concentration, the carbon element on the electrode electrolyte interface decreases, the organic component decreases, and the inorganic component increases. When the concentration reaches 4 mol / L, the carbon content decreases to 47%.
[0096] The negative electrode materials obtained in Example 1, Example 3 and Example 5 were immersed in a commercial sodium ion battery electrolyte, wherein the electrolyte was a 1 mol / L sodium bis(fluorosulfonyl)imide solution in ethylene glycol dimethyl ether, and immersed for 50 h. XPS was used to characterize the changes in the element content of the negative electrode materials corresponding to each example before and after immersion, as shown in FIG. Figure 6 As shown, it can be seen that the solubility of each element in the solution of the negative electrode material corresponding to 1 mol / L is the largest, and the solubility of each element in the solution of the negative electrode material corresponding to 4 mol / L is the smallest. The dissolution of each element is effectively inhibited and is much smaller than other negative electrode materials.
[0097] The component changes of the electrode-electrolyte interface on the negative electrode material in each electrolyte are observed, forming schematic diagrams shown in Figures 7(a) to 7(c). The electrode-electrolyte interface formed by the negative electrode material corresponding to 0.2 mol / L is shown in Figure 7(a), forming an electrode-electrolyte interface rich in organic components. When immersed in an electrolyte (1 mol / L sodium bis(fluorosulfonyl)imide in ethylene glycol dimethyl ether solution), the organic components are dissolved; the electrode-electrolyte interface formed by the negative electrode material corresponding to 1 mol / L is shown in Figure 7(b), forming The electrode electrolyte interface formed by the negative electrode material corresponding to 4 mol / L is shown in Figure 7(c), which forms an electrode electrolyte interface rich in inorganic components. When immersed in the electrolyte (1 mol / L sodium bis(fluorosulfonyl)imide in ethylene glycol dimethyl ether solution), the entire interface is almost insoluble, the dissolution is effectively inhibited, and the interface stability is high.
[0098] Effect Test 4: Coulombic Efficiency of Full Battery in the First Week
[0099] The full batteries prepared in Example 7 and Example 8 were subjected to charge and discharge cycles, and the charge and discharge curves and the first cycle coulombic efficiency were tested. Figure 8 As shown, it can be seen that the full battery (insoluble SEI) formed by the negative electrode material assembled after pretreatment with high-concentration electrolyte (4M) suppressed the excessive electrode-electrolyte interface growth and other side reactions in the first week, achieving a high first-week coulomb efficiency of 90.29%. The full battery (control group SEI) formed by the negative electrode material assembled after pretreatment with conventional concentration electrolyte (1M) could not suppress the dissolution and growth of the electrode-electrolyte interface, and thus only had a low first-week coulomb efficiency of 80.69%. Effect Test 5 - Capacity retention rate of the full battery after 900 cycles
[0100] The full batteries prepared in Example 7 and Example 8 were subjected to charge and discharge cycles for 900 cycles, and the changes in the specific capacity of the batteries during the cycles were recorded. Fig. 9 As shown, it can be seen that the sodium ion full battery (insoluble SEI) assembled from the negative electrode materials pretreated with high-concentration electrolyte maintained a high capacity retention rate of 80.0% after 900 cycles, while the full battery (control group SEI) assembled from the negative electrode materials pretreated with conventional concentration electrolyte only maintained a lower level of 46.8%.
[0101] Effect Test 6 - Coulombic efficiency of full battery after 900 cycles
[0102] The full batteries prepared in Example 7 and Example 8 were subjected to charge and discharge cycles for 900 cycles, and the changes in the coulombic efficiency of the full batteries during the cycles were recorded, as shown in FIG. Fig.10As shown, it can be seen that the sodium ion full battery (insoluble SEI) formed by the negative electrode material pretreated with high concentration electrolyte achieved a high average coulombic efficiency of 99.95%, while the full battery (control group SEI) assembled by the negative electrode material pretreated with conventional concentration electrolyte had a lower average coulombic efficiency of only 99.02%.
[0103] The full batteries in Example 11 and Example 12 were subjected to charge and discharge cycles, and the changes in the specific capacity and coulombic efficiency of the batteries during the cycles were recorded. The test showed that after 900 cycles, the capacity retention rate of the full batteries in Example 11 and Example 12 was much higher than that of the full batteries corresponding to the negative electrode materials pretreated with 1 mol / L electrolyte. The coulombic efficiency of the full batteries obtained in Example 11 and Example 12 was higher than that of the full batteries corresponding to the negative electrode materials pretreated with 1 mol / L electrolyte. When immersed in an electrolyte (1 mol / L sodium bis(fluorosulfonyl)imide in ethylene glycol dimethyl ether solution), the entire interface was almost insoluble, dissolution was effectively suppressed, and the interface stability was high.
[0104] From the above data, it can be seen that the pre-formed insoluble electrode-electrolyte interface on the negative electrode material helps to improve the stability of the interface and the coulombic efficiency of the battery. When the organic component content on the electrode-electrolyte interface of the negative electrode material is less than the inorganic component content or the carbon content is less than 50% or the loss rate of the interface component is less than 15% after being immersed in an organic solvent for 50 hours, the assembled full battery has a better effect.
[0105] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for pretreating a negative electrode material for a sodium ion battery, characterized in that: The method comprises the following steps: obtaining a negative electrode material body; Constructing a pre-treatment battery system: constructing a pre-treatment battery system with the negative electrode material body as the working electrode, the concentration of the electrolyte in the pre-treatment battery system is greater than the concentration of the electrolyte in the target battery system, the pre-treatment battery system is a battery system for pre-treating the negative electrode material body, the pre-treatment battery system is a sodium ion battery, and the target battery system is a battery system to be constructed with the pre-treated negative electrode material body as the negative electrode; Performing a charge-discharge cycle on the pre-processed battery system: performing a charge-discharge cycle on the constructed pre-processed battery system to form an electrode electrolyte interface on the negative electrode material body; The negative electrode material body is taken out to obtain the pretreated negative electrode material.
2. The method for pretreating anode materials for sodium ion batteries according to claim 1, characterized in that: The pretreatment battery system is constructed in one of the following ways: ——Use the negative electrode material as the working electrode and sodium metal as the counter electrode to construct a half-cell system; ——Build a full battery system with the negative electrode material as the negative electrode and the sodium battery positive electrode material as the positive electrode.
3. The method for pretreating anode materials for sodium ion batteries according to claim 1, characterized in that: The concentration of the electrolyte in the pretreatment battery system is higher than 1.8 mol / L, preferably higher than 4 mol / L.
4. The method for pretreating anode materials for sodium ion batteries according to claim 1, characterized in that: The negative electrode material body is a hard carbon electrode material or a copper electrode material; When the hard carbon electrode material is used as the negative electrode material, the sodium ion battery system is charged and discharged at a current of (0.1-1) C and a voltage of (0.0002-2) V. When the copper electrode material is used as the negative electrode material, the sodium ion battery system performs charge and discharge cycles at a current of (5-100) μA and a voltage of (0.0002-2) V.
5. The method for pretreating anode materials for sodium ion batteries according to claim 1 or 4, characterized in that: During the charge and discharge cycle of the pre-treatment battery system, the number of cycles is at least 1, preferably more than 3.
6. The method for pretreating anode materials for sodium ion batteries according to claim 1, characterized in that: The electrolyte components in the pretreatment battery system are the same as or different from the electrolyte components in the target battery system. The electrolyte of the pretreatment battery system or / and the target battery system includes a sodium salt and a solvent, the solvent is an organic solvent, and the sodium salt and the solvent at least meet one of the following requirements: The sodium salt is a combination of one or more of sodium hexafluorophosphate, sodium bis(fluorosulfonyl)imide, sodium nitrate, sodium perchlorate, sodium bis(trifluoromethylsulfonyl)imide, sodium trifluoromethanesulfonate, sodium chloride, sodium tetrafluoroborate, sodium methanesulfonate, sodium trifluoromethylsulfonate, sodium bis(oxalatoborate), sodium difluorooxalatoborate, sodium difluorophosphate, sodium difluorobis(oxalatophosphate), and sodium hexafluoroarsenate; The solvent is a combination of one or more of ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, propylene carbonate, diethyl carbonate, dioxolane, ethyl methyl carbonate, dimethyl carbonate, vinylene carbonate, fluoroethylene carbonate, and tetrahydrofuran; Preferably, the sodium salt in the pretreatment battery system is sodium bis(fluorosulfonyl)imide, and the solvent is ethylene glycol dimethyl ether.
7. The method for pretreating anode materials for sodium ion batteries according to claim 4, characterized in that: The preparation method of the hard carbon electrode is: hard carbon powder is mixed with a binder and a conductive agent in a dispersant in a set ratio, and the mixture is coated on a conductive current collector; the coated hard carbon electrode is vacuum dried to obtain a hard carbon electrode, wherein the binder is preferably polyvinylidene fluoride, the conductive agent is conductive carbon black, and the dispersant is N-methylpyrrolidone.
8. The method for pretreating anode materials for sodium ion batteries according to claim 1, characterized in that: The organic component content of the components at the electrode electrolyte interface is less than 70%, and the atomic percentage content of the carbon element is less than 60%, preferably the atomic percentage content of the carbon element is less than 50%.
9. A sodium ion battery negative electrode material, characterized in that: The surface of the negative electrode material body contains a preformed electrode electrolyte interface.
10. The negative electrode material for sodium ion batteries according to claim 9, characterized in that: The electrode-electrolyte interface satisfies one or more of the following combinations, preferably satisfies all three of the following simultaneously: ——the content of organic components at the electrode electrolyte interface is less than the content of inorganic components; - After the electrode electrolyte interface is immersed in an organic solvent for 50 hours, the component loss rate in the electrode electrolyte interface is less than 15%; - The carbon content in the components at the electrode electrolyte interface is less than 60%, preferably less than 50%.
11. The negative electrode material for sodium ion battery according to claim 9, characterized in that: Obtained by the pretreatment method according to claims 1 to 8.
12. A sodium ion battery, characterized in that: A sodium ion battery constructed using the pretreated sodium ion battery negative electrode material obtained in claim 1 as the negative electrode or using the negative electrode material described in claim 9 as the negative electrode.
Citation Information
Patent Citations
Sodium-ion battery electrolyte, sodium-ion battery and preparation method
CN114156543A
Method for pre-sodium treatment of negative electrode, pre-sodium-treated negative electrode, and lithium secondary battery comprising same
CN114207866A
Sodium-ion battery negative plate based on ether electrolyte and sodium-ion battery
CN117747950A
Sodium-ion secondary battery
WO2024046110A1
